2021
DOI: 10.1073/pnas.2004832117
|View full text |Cite
|
Sign up to set email alerts
|

Frequent loss of heterozygosity in CRISPR-Cas9–edited early human embryos

Abstract: CRISPR-Cas9 genome editing is a promising technique for clinical applications, such as the correction of disease-associated alleles in somatic cells. The use of this approach has also been discussed in the context of heritable editing of the human germ line. However, studies assessing gene correction in early human embryos report low efficiency of mutation repair, high rates of mosaicism, and the possibility of unintended editing outcomes that may have pathologic consequences. We developed computational pipeli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 53 publications
3
90
0
Order By: Relevance
“…10d), which suggests that long deletions or rearrangements occurred in approximately 14% of BCL11A alleles. This frequency is consistent with recent findings in edited human embryos 26 . Together, these results are concordant with previous findings 14 and suggest that base editor treatment of human HSPCs causes less stimulation of the p53 pathway and fewer large target site perturbations than Cas9 nuclease treatment.…”
Section: Effects Of Nuclease and Abe Treatmentsupporting
confidence: 93%
“…10d), which suggests that long deletions or rearrangements occurred in approximately 14% of BCL11A alleles. This frequency is consistent with recent findings in edited human embryos 26 . Together, these results are concordant with previous findings 14 and suggest that base editor treatment of human HSPCs causes less stimulation of the p53 pathway and fewer large target site perturbations than Cas9 nuclease treatment.…”
Section: Effects Of Nuclease and Abe Treatmentsupporting
confidence: 93%
“…In summary, we report the most detailed molecular analysis to date of the formation and propagation of complex chromosome alterations after genome editing-mediated and spontaneous missegregation events in the mouse embryo. In contrast with other recent studies 4 , 5 , 20 , we are able to deeply sequence most cells from 8-cell embryos, allowing us to reconstruct the karyotypic history of complex events including micronuclei and chromosome bridge formation. Importantly, even the ~2-3-fold increase in micronucleation events after Cas9 treatment can be biologically significant due to the ongoing instability and breakage amplification that occurs after chromosome breakage leads to either micronucleation or further bridge formation 10 .…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, Adikusuma et al 3 observed deletions of up to 2.3 kb near the target site in mouse embryos. Furthermore, after editing of human pre-implantation embryos, several studies identified larger, megabase-scale deletions 4 , 5 . Counterintuitively, CRISPR-Cas9 editing in embryos also commonly leads to the loss of the entire targeted chromosome 5 , the cause of which is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, safety issues regarding genome ON-target integrity lack in-depth exploration. In addition to small Indels, a single ON-target DSB can lead to large deletions up to several kilobases in size, symmetrical or not, in mouse embryos 8 , 9 , in mouse hematopoietic progenitors, in human immortalized differentiated cells 10 and human embryos 11 . Recently, we reported that CRISPR-Cas9 can even cause megabase-scale chromosomal truncations targeting Chromosome 10q (Chr10q) in two human cell lines and in human primary fibroblasts deficient for the tumor suppressor p53 12 .…”
Section: Introductionmentioning
confidence: 99%